Temperature-dependent short channel effects in nanoscale double gate FinFETs: A comparative study - Nura Muhammad Shehu,; Garba Babaji,; Mutari Hajara Ali, (International Journal of Scientific World, 2023)
This work investigates the impact of temperature variation on Short Channel Effects (SCEs).  Gallium Arsenide (GaAs), Gallium Antimonide (GaSb), Gallium Nitride (GaN) and Silicon (Si) are the channel materials that are investigated. The study examines phenomenal metrics such as Drain Induced Barrier Lowering (DIBL), Subthreshold Swing (SS), Threshold Voltage Roll-off, On-current and Transconductance using PADRE Simulator. The results revealed that GaAs-FinFET excels in terms of DIBL, threshold voltage, transconductance and on-current at higher temperatures. On the other hand, GaN-FinFET excels in terms of SS at lower temperatures. These findings contribute to the understanding of temperature effects on nanoscale double gate FinFETs, aiding their optimization for diverse electronic devices.